The Mechanics of Malaria Parasite Invasion of the Human Erythrocyte - Towards a Reassessment of the Host Cell Contribution - Koch,M; Baum,J (Cellular Microbiology, 2016)
Despite decades of research, we still know little about the mechanics of Plasmodium host cell invasion. Fundamentally, while the essential or non-essential nature of different parasite proteins is becoming clearer, their actual function and how each comes together to govern invasion are poorly understood. Furthermore, in recent years an emerging world view is shifting focus away from the parasite actin–myosin motor being the sole force responsible for entry to an appreciation of host cell dynamics and forces and their contribution to the process. In this review, we discuss merozoite invasion of the erythrocyte, focusing on the complex set of pre-invasion events and how these might prime the red cell to facilitate invasion. While traditionally parasite interactions at this stage have been viewed simplistically as mediating adhesion only, recent work makes it apparent that by interacting with a number of host receptors and signalling pathways, combined with secretion of parasite-derived lipid material, that the merozoite may initiate cytoskeletal re-arrangements and biophysical changes in the erythrocyte that greatly reduce energy barriers for entry. Seen in this light Plasmodium invasion may well turn out to be a balance between host and parasite forces, much like that of other pathogen infection mechanisms.